Aceh Store : Sebuah Sistem Informasi Geografis Penjualan Berbasis Android (Journal Digital Technology Trend, 2022)
The purpose of this study is to design an application that can help users find information on sales locations in Aceh. The several stages of work consist of; data collection, analysis, application design and design, implementation, and testing and evaluation. Based on the results of the activity of designing an android-based geographic information system for sales locations, Based on the results of the activities of designing an Android-based Aceh Store geographic information system, the author can conclude that; the system can be used to manage the results of data on food and beverage sellers in Aceh Province which is carried out online properly because the data is centralized on one server and at any time needed it can be searched easily, and the system can make it easier for users or visitors to get information about product sellers. which is specifically in Aceh Province.